Reviving the Market for Corporate Control - Leechor, Chad (World Bank, Washington, DC, 2012)
Changes in corporate control-through mergers, takeovers, acquisitions, divestitures, and the like-enhance shareholders' value. They allow the businesses to be transferred to the control of new owners who can put business assets to work more efficiently. In most countries, however, the market for corporate control is significantly restricted by anti-takeover laws and business practices used to entrench management, such as poison pills, heavy debt, pyramid schemes, and cross-holdings of equity. The key to overcoming these obstacles is to restructure incentives-by requiring business groups to disclose intercorporate ownership and banks to limit connected lending, by ensuring that bankruptcy law allows effective transfer of control, and by removing regulatory barriers to takeovers. Many studies of mergers, takeovers, acquisitions, and divestitures have confirmed that these control transactions generally maximize shareholders' value (Jensen and Ruback 1983). The gain in value is most visible in target firms' stock prices following announcements of takeover attempts or merger agreements. Even in the most advanced markets, where control transactions are common, stock prices increase 20 to 30 percent on average, depending on the type of transaction (Jarrell, Brickley, and Netter 1988). This gain represents one part of the increased business value that the acquirer is prepared to share with the target firm.